El principio de inmediación en materia penal, una mirada desde las sentencias de los tribunales de México, Colombia y Chile - Elizalde Castañeda, Rodolfo Rafael (2026)
The objective of this paper is to research and analyze the interpretation and application of the principle of immediacy in criminal matters, based on the study of some judgments issued by courts of justice of Mexico, Colombia and Chile, which we have chosen. Therefore, we will use the comparative method to understand the doctrinal, constitutional, legal and jurisprudential experience of the aforementioned principle in those specific cases, to find out if there have uniform criteria in those interpretations and applications of the immediacy principle.